NEW MODELS OF VENTURE FINANCING IN UZBEKISTAN (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Venture financing plays a pivotal role in driving innovation and economic growth, particularly in emerging economies like Uzbekistan. This article delves into the evolving landscape of venture financing in Uzbekistan, examining recent developments and new models that are shaping the entrepreneurial ecosystem. Through a comprehensive analysis of government policies, private investment trends, and emerging startup ecosystems, this study highlights the transformative impact of venture financing on Uzbekistan's economy. By showcasing case studies of successful ventures and exploring the challenges and opportunities inherent in this dynamic landscape, this article provides valuable insights into the future trajectory of venture financing in Uzbekistan and its role in fostering innovation and entrepreneurship.